Peran Guru PAI dalam Pembinaan Akhlak Peserta Didik di Indonesia - Najma Fajriani; Askari Zakariah; Novita Novita (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The cultivation of students' morals by Islamic Education teachers is of utmost importance in both worldly and spiritual life. Its aim is to shape the character of students with noble virtues according to Islamic teachings, such as obedience to Allah and His Messenger, and respect for parents. The process of moral upbringing is conducted continuously and systematically to transform and instill positive attitudes and behaviors in students, with the goal of achieving happiness in both this world and the hereafter.This study employs a literature review approach to identify the role of Islamic Education teachers in nurturing students' morals. Teachers of Islamic Education bear moral and professional responsibilities to provide continuous and guided guidance so that students can internalize Islamic moral values in their daily lives.The conclusion of this study affirms that the cultivation of students' morals by Islamic Education teachers is a strategic effort to shape a generation that is of high quality both morally and spiritually. This effort is crucial in preparing students to face life's challenges and to pursue happiness in both the present life and the afterlife